When not bound by gravity it is possible to grow almost indefinitely large : about the sperm whale and how we perceive it - Christensen, Lise Haurum (Konstfack, Institutionen för Konst (K), 2011)
It dives the deepest seas of the world. In total darkness it hunts its pray. On its head the circular scars tell a story of the many encounters with an almost unknown creature - the giant squid. It lives most of its life far away from shore at the open oceans. There it is seen resting in the light of the surface clearing its lungs and gathering oxygen for yet another dive into the blue abyss underneath. In its head the sperm whale carries the largest brain ever to have existed on earth. But what are its thoughts?